Reconfiguring SME Value Through Branding: A Resource-Based Perspective from Local Enterprises in Rote Ndao - Jusuf Aboladaka; Donny Mercys Bessie; Robert A. Serang; Alfred G.O Kase (Global Research and Collaboration, 2026)
Strengthening the competitiveness of Small and Medium Enterprises (SMEs) through branding strategies is a crucial issue amidst limited market access and low product differentiation, particularly in local economy-based areas such as Rote Ndao Regency. This study aims to analyze the application of branding models to increase the selling value of SME products and identify relevant strengthening strategies based on local wisdom. The research employed a qualitative approach with a case study design, using data collection techniques such as in-depth interviews, observation, and document analysis with selected SMEs using purposive sampling. Data analysis was conducted through interactive data reduction, presentation, and conclusion drawing. The results indicate that the application of branding elements, including brand identity, positioning, brand communication, storytelling, and brand experience, significantly increases the selling value of SME products. SMEs that implement branding in a more structured manner tend to have higher perceived value, stronger market appeal, and broader market penetration capabilities. However, limited resource capacity, low branding literacy, and minimal use of digital technology remain major obstacles to optimizing this strategy. The implications of this research emphasize that branding is not merely a promotional tool, but rather a strategic asset based on internal resources capable of creating sustainable competitive advantage. Therefore, policy interventions such as intensive mentoring, strengthening digital capacity, and integrating local values ​​into branding strategies are needed to encourage the transformation of SMEs into more competitive markets.